Methods in Learning: An Introduction and Conceptual Review - Alias, Hamzah; Basri, Hasan; Saprin, Saprin; Yuspiani, Yuspiani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Effective learning in elementary education is key to creating a generation capable of competing in the global era. Various methods, including student-centered learning, the use of technology in learning, project-based learning, and differentiated learning approaches, have been shown to increase student engagement, critical thinking skills, and problem-solving. Therefore, this study aims to analyze various effective learning methods through a conceptual literature review. Using a literature review or library research approach, this study collects and analyzes various relevant sources to understand the concepts and applications of learning methods. This research finding demonstrates that effective learning methods are crucial for improving the quality of learning and achieving educational goals. This research identifies various learning methods in education: lecture method, discussion method, demonstration method, experimental method, field trip method, practice method, simulation method, debate method, mind mapping method, discovery method, and problem-solving method. This research demonstrates that each learning method has advantages and disadvantages, and therefore, it is important to select and use them appropriately according to the context and learning objectives. Many aspects related to learning methods still require further research, such as the development of more effective and contextual learning methods. However, challenges such as unequal access to technology and teacher readiness need to be addressed to ensure that every student has optimal learning opportunities. The results of this study are expected to contribute to the development of more effective and innovative learning practices.